Pengaruh Hambatan Samping Terhadap Kinerja Lalu Lintas Pada Jalan Inspeksi Pam (Studi Kasus: Pasar Tello) - Gerald Mangiri; Benyamin Tanan; Monika Datu Mirring Palinggi (Paulus Civil Engineering Journal, 2023)
One of the factors that can reduce the level of traffic performance is an increase in vehicle volume and side barriers on the road. Along the pam Inspection road there are traditional shopping centers so that the area is full of community activities, this causes traffic problems that cause congestion. This study aims to decide the traffic flow and the crash of side barriers on the level of drench on the pump inspection road. Data assembly was carried out for three days. The data collected included prime data and secondary data, where prime data was obtained from direct surveys in the field by collecting traffic volume data, side obstacle data, vehicle speed data and road geometric data. While secondary data, namely population data, then data processing was carried out using the 2014 Indonesian Road Capacity Guidelines (PKJI). Monday with a total of 1292.9 events/hour, the degree of saturation obtained is 0.91, and the actual speed obtained in each segment is 5.85 km/hour in segment 1 and 4,356 in segment 2 where the traffic flow is experiencing congestion. and vehicle movement speed is controlled during peak hours.